A colorimetric and fluorescent pH probe for imaging in E. coli cells. Issue 2 (4th January 2017) - Chao, Jianbin; Song, Kailun; Wang, Huijuan; Li, Zhiqing; Zhang, Yongbin; Yin, Caixia; Huo, Fangjun; Wang, Juanjuan; Zhang, Ting
Abstract : MDAK exhibited turn-off fluorescence as the pH decreased. Simultaneously, the color of the solution changed from yellow to colorless. Abstract : A colorimetric and fluorescent pH probe 1-(4-methylphenyl)-3-(4-dimethylaminophenyl) acrylketone (MDAK ) was facilely prepared. The probe exhibited strong pH-dependent behavior and responded linearly and rapidly to minor pH fluctuations within the range of 1.53–3.96. In addition, MDAK displayed a notably large Stokes shift of 121 nm.MDAK possessed a highly selective response to H + over other metal ions, amion acids and displayed good photostability and excellent reversibility. Furthermore, it can be applied to visualize extreme acidity in E. coli cells.